Anti-MRSA activity of isoplagiochin-type macrocyclic bis(bibenzyl)s is mediated through cell membrane damage. Issue 13 (1st July 2015) - Onoda, Kenji; Sawada, Hiromi; Morita, Daichi; Fujii, Kana; Tokiwa, Hiroaki; Kuroda, Teruo; Miyachi, Hiroyuki
Graphical abstract: Abstract: We synthesized three geometrical isomers of a macrocyclic bis(bibenzyl) based on isoplagiochin, a natural product isolated from bryophytes, and evaluated their antibacterial activity towards methicillin-resistant Staphylococcus aureus (anti-MRSA activity). The isomer containing a 1, 4-linked ring (5 ) showed only weak activity, whereas the isomers containing a 1, 3-linked (6 ) or 1, 2-linked (7 ) C ring showed potent anti-MRSA activity. Molecular dynamics calculations indicated that these differences are probably due to differences in the conformational flexibility of the macrocyclic ring; the active compounds6 and7 were more rigid than5 . In order to understand the action mechanism of anti-MRSA activity, we investigated the cellular flux of a fluorescent DNA-binder, ethidium bromide (EtBr), in the presence and absence of these macrocycles. The active compound6 increased the levels of EtBr inflow and outflow in S. aureus cells, as did our potent anti-MRSA riccardin derivative (4 ), indicating that these compounds increased the permeability of the cytoplasmic membrane. Inactive5 had no effect on EtBr inflow or outflow. Furthermore, compound6 abrogated the normal intracellular concentration gradients of Na + and K + in S. aureus cells, increasing the intracellular Na + concentration and decreasing the K + concentration, while5 had no such effect. These results indicate that anti-MRSA-active macrocyclic bis(bibenzyl) derivatives directly damage the gram-positive bacterial membrane, resulting in increased permeability.